2005
DOI: 10.1111/j.1600-0447.2005.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant combinations: epidemiological considerations

Abstract: There appears to be considerable variability in the data concerning combined prescription of antidepressants, with differences arising depending on the type of physician, the type of patient or illness and the geographical area. It is also unclear how closely research findings parallel with what doctors do in everyday practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…This may be due to the characteristics of the patient population in these countries. On the other hand, all investigators in Austria were specialists and may treat depression more aggressively than PCPs to achieve full remission [1]. Moreover, it has been recommended in the UK, for example, that antidepressant combinations should only be initiated under specialist supervision [22].…”
Section: Differences Among Countriesmentioning
confidence: 99%
“…This may be due to the characteristics of the patient population in these countries. On the other hand, all investigators in Austria were specialists and may treat depression more aggressively than PCPs to achieve full remission [1]. Moreover, it has been recommended in the UK, for example, that antidepressant combinations should only be initiated under specialist supervision [22].…”
Section: Differences Among Countriesmentioning
confidence: 99%
“…We were alarmed on reading the results of a recent survey of Australian doctors working in mental health that reported that 79% had used combination antidepressants in the treatment of depression 1 . This figure is in stark contrast to rates published from similar international surveys that suggest the use of combination antidepressants is between 2 and 15% 2 . Even in the home of this practice, combination antidepressants appear to be used by only 3% of psychiatrists in the United States 3 .…”
mentioning
confidence: 92%
“…There are different reasons why a patient fails to respond or responds only partially to a prescribed antidepressant. These include pharmacogenetic variations, problems associated with the pharmacokinetics of the prescribed drug and possible interactions with other medication, as well as the patient's general state of health and the presence of other psychiatric illness or substance abuse (Agüera, et al, 2005;Wijeratne and Sachdev, 2008).…”
Section: Introductionmentioning
confidence: 99%